Ketukangan di Jawa Awal Abad Ke-20 dalam Teks Serat Seserepan Katukangan Sawetawis - muhammad bilal radhitya prahasya; Munawar Holil (Perpustakaan Nasional RI, 2022)
This study examined manuscript Serat Seserepan Katukangan Sawetawis (SSKS) and the texts contained in it. The manuscript is registered as a collection of the Central Library of the University of Indonesia with the collection code number NR 378-KR.11. This research was conducted using a qualitative approach in the context of the study of Javanese manuscripts whose texts discuss traditional craftsmanship and architecture. The purpose of this study was to reveal that the SSKS manuscript is a record of the craftsmanship in Java in the early 20th century through systematic work of philology. The text content analysis was conducted using descriptive and interpretive methods in order to reveal the craftmanship content in the SSKS texts. The interpretations of the text data were then linked to expert opinions or research findings from other disciplines such as the field of building construction, soil science, and occupational safety and health (K3). The content analysis of SSKS texts was carried out, so that the content of the SSKS manuscript could be actualized in accordance with the conditions in the current development era. The findings of this study are (1) the SSKS manuscript is an important document in the field of craftsmanship, and it was written as a guide for craftsmen to make or build something, (2) the craftsmanship skill mastered by masons based on SSKS text include (a) relating to 25 types of tools with their respective functions commonly used by masons, (b) inspection and clearing of land from trees and shrubs for foundation construction, (c) knowledge of the five criteria for soil types in the vicinity where a building’s foundation will be built, (d) knowledge of basic principles regarding rock types relating to making good quality, and (e) warnings regarding the capacity of space capacity and air when digging wells.